Polarization-sensitive OFDI findings of vascular tissue response following drug-eluting stent implantation in patients with coronary artery disease. (25th November 2020) - Otsuka, K; Villiger, M; Van Zandvoort, L.J.C; Neleman, T; Karanasos, A; Dijkstra, J; Nadkarni, S.K; Regar, E; Daemen, J; Bouma, B.E
Abstract:  : Intravascular polarimetry (IVP) with polarization-sensitive (PS-) optical frequency domain imaging (OFDI) measures polarization properties of the coronary arterial wall in parallel with the conventional OFDI images (Figure 1A). Tissues rich in collagen and smooth muscle cells (SMCs) appear birefringent, while the presence of lipid and macrophages causes depolarization. Because drug-eluting stents (DES) are designed to prevent SMC proliferation and collagen deposition, we hypothesized that neointimal tissue would exhibit low birefringence. The accumulation of lipid-laden macrophages characteristic of neoatherosclerosis should result in notable depolarization. Methods: This study included 19 DES imaged with PS-OFDI in 13 patients (median follow-up period of 1.5 years). Coronary segments stented >90 days were analyzed every 1 mm. We analyzed polarization properties of the neointima in a total of 455 frames, and in additional 97 frames of native atherosclerosis remote from the stented segments. Neointima, delineated by the lumen and the inner boundary of the stent, was manually segmented in the intensity images using MATLAB. The median birefringence in all areas of the segmented neointima featuring a depolarization of ≤0.2 and the median depolarization across the entire neointima were computed for each frame after masking the guidewire shadow. Frames presenting intensity features of macrophages, lipid or calcifications extending to at least one adjacent frame were classified as neoatherosclerosis (n=112), and otherwise as normal neointima (n=343). For comparison with neoatherosclerosis, polarization properties of native atherosclerosis (n=97) were measured. We also categorized all frames of a stented segment according to the presence of in-stent restenosis (ISR) and/or stent thrombosis (ST) (204 frames from 5 patients). A generalized linear model using a generalized estimating equation or one-way ANOVA was used for statistical analysis. Results: The major findings of the present study are: 1) neoatherosclerosis exhibited lower birefringence than native atherosclerosis (p<0.001, Figure-1B); 2) depolarization was positively associated with neoatherosclerosis (β=0.86, p<0.001) and ISR/ST (β=0.72, p=0.002), while birefringence was not (Figure 1C); 3) birefringence was positively correlated with the duration after DES implantation (β=5.22×10 –3, p<0.001, Figure 1D). For the detection of neointimas within stents with ISR, the best cut-off value for depolarization was 0.033 with a sensitivity of 77% and a specificity of 57% (AUC=0.72). For comparison, using only conventional OFDI parameters to detect stents with ISR, the AUC were 0.52 for calcium area, 0.62 for lipid arc, and 0.63 for macrophage accumulations. Conclusions: This study suggests that IVP provides quantitative assessment of vascular healing after DES implantation and may help clinical decision making in patients at high risk of stent failure. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was supported by the National Institutes of Health.